2015
DOI: 10.3171/2014.10.jns141317
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on cerebellar tonsil position in healthy subjects and patients with Chiari malformation

Abstract: OBJECT It is unclear if there is a relationship between Chiari malformation Type I (CM-I) and body mass index (BMI). The aim of this study was to identify the relationship between BMI and cerebellar tonsil position in a random sample of people. METHODS Cerebellar tonsil position in 2400 subjects from a cohort of patients undergoing MRI was measured. Three hundred patients were randomly selected from each of 8 age groups (from 0 to 80 years). A subject was then excluded if he or she had a posterior fossa mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…IIH in obese patients is not likely to be the primary cause of cerebellar tonsillar herniation of greater than 5 mm as a review of over 1300 mri images in which the BMI of the patient was known showed no relationship between the BMI and the position of the tonsils [2]. It is clear however that the brain volume and ICP are related and dependent on dural venous sinus pressure.…”
Section: Conjecture Regarding the Interaction Of Obesity With Cm1mentioning
confidence: 99%
See 2 more Smart Citations
“…IIH in obese patients is not likely to be the primary cause of cerebellar tonsillar herniation of greater than 5 mm as a review of over 1300 mri images in which the BMI of the patient was known showed no relationship between the BMI and the position of the tonsils [2]. It is clear however that the brain volume and ICP are related and dependent on dural venous sinus pressure.…”
Section: Conjecture Regarding the Interaction Of Obesity With Cm1mentioning
confidence: 99%
“…From the late 1980's it has become clear that the majority of patients who have significant degrees of tonsillar descent are asymptomatic and that tonsillar ectopia is not rare. It is estimated that as many as 0.5% of individuals would have scans that would be read as having CM1 [2]. What makes the difference between individuals with cerebellar dystopia with incapacitating symptoms and others with identical imaging who are asymptomatic?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation